2023
DOI: 10.1038/s41598-023-35156-x
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil yield and compositions of Dracocephalum moldavica L. in intercropping with fenugreek, inoculation with mycorrhizal fungi and bacteria

Abstract: Intercropping is one of the most important components of sustainable agriculture. The effects of chemical fertilizer (CF), arbuscular mycorrhizal fungi (AMF) (Glomus sp.) and AMF + nitrogen-fixing bacteria (NFB) including Azospirillum and Azotobacter (AMF + NFB) was studied on essential oil yield and compositions of Moldavian balm (Mb) (Dracocephalum moldavica L.) in sole cropping and intercropping with fenugreek (F) (Trigonella foenum-graecum L.). The experiment was conducted during 2020 and 2021 growing seas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This increase in plant height can be attributed to competition for more light interception and limited light penetration through the canopy, as well as a lack of decomposition of auxin hormone under these intercropping conditions. Furthermore, a recent study by Amiriyan Chelan et al [ 30 ] focused on intercropping Dracocephalum moldavica L. with fenugreek ( Trigonella foenum-graecum L.). The researchers observed that the height of both species increased in the intercropping system compared to mono cropping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in plant height can be attributed to competition for more light interception and limited light penetration through the canopy, as well as a lack of decomposition of auxin hormone under these intercropping conditions. Furthermore, a recent study by Amiriyan Chelan et al [ 30 ] focused on intercropping Dracocephalum moldavica L. with fenugreek ( Trigonella foenum-graecum L.). The researchers observed that the height of both species increased in the intercropping system compared to mono cropping.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of LER values revealed that the weedy plots exhibited the highest values, indicating a greater efficiency in land utilization within those particular conditions. Previous research has consistently demonstrated that the superiority of intercropping can be attributed to various factors, including distinct morphological properties and growth patterns, as well as the inherent ability of intercropping components to efficiently utilize vital resources such as soil, moisture, light, and essential nutrient elements [ 30 , 37 , 38 ]. Wang et al [ 38 ], reported that a jujube–cotton intercropping system had advantages in LER, yield, and income.…”
Section: Discussionmentioning
confidence: 99%